KAJIAN PEMANFAATAN LAHAN PEMUKIMAN, PARIWISATA DAN BUDIDAYA TAMBAK BERDASARKAN UNDANG-UNDANG NOMOR 1 TAHUN 2014 DI KAWASAN PESISIR KABUPATEN TULUNGAGUNG - Haniah, Rafiqatul; Putranto, Anggoro (Universitas Negeri Makassar, 2024)
The coastal area in Tulungagung has abundant natural resource potential, various types of biodiversity and great economic potential. Coastal ecosystems supported by diversity must be utilized and managed properly, which can provide benefits to the surrounding community and minimize losses due to the use of the environment. The coastal area develops dynamically, the dynamics of the use coastal area in Tulungagung is dominated by land use as settlements, tourism and pond cultivation. Economic factors encourage the community to use coastal areas as settlements, tourism and shrimp pond cultivation in Tulungagung. The use of coastal areas must also refer to applicable laws, one of which is law number 1 of 2014 concerning the Management of coastal areas and small islands, so that it can minimize the risk of natural disasters, considering that coastal areas are a transition area from land to sea. The purpose of this study is to examine the suitability of land use for settlements, tourism and pond cultivation in coastal areas based on law number 1 of 2014. This type of research is qualitative research, with primary and secondary data. Methods used with field observation, documentation, interviews. The results of the study show that there is land use for settlements in coastal areas that is not in accordance with its designation. The use of land for tourism activities is still in accordance with the land allocation, because people who make a living in the tourism sector are more orderly in obeying the rules of the relevant agencies. As for the development of shrimp pond cultivation, it is in accordance with land allocation, pond cultivation locations are close to the sea because they consider the need for water resources for pond needs and young locations are accessed for feed distribution and pond product production.